Outcomes Associated With 4‐Factor Prothrombin Complex Concentrate Administration to Reverse Oral Factor Xa Inhibitors in Bleeding Patients. (9th November 2020) - Highsmith, Emily A.; Morton, Celia; Varnado, Sara; Donahue, Kevin R.; Sulhan, Suraj; Lista, Annette
Abstract: Compared with vitamin K antagonists (VKAs), oral factor Xa inhibitors are associated with at least equivalent efficacy and a lower incidence of major bleeding. Despite this benefit, bleeding remains the most common adverse event. Prior to the approval of andexanet alfa, alternative agents such as 4‐factor prothrombin complex concentrate (4F‐PCC) were utilized for reversal. This was a retrospective, descriptive study conducted on patients 18 years of age or older who received 4F‐PCC for reversal of oral factor Xa inhibitors‐associated bleeding. Patients were excluded if they received a VKA or dabigatran in the previous 48 hours. A subgroup analysis comparing 4F‐PCC with andexanet alfa was conducted on patients who met the inclusion and exclusion criteria of the ANNEXA‐4 trial. The primary end point of this study was to evaluate the incidence of hemostasis and associated dosing strategies in patients receiving 4F‐PCC for reversal of oral factor Xa inhibitors‐associated bleeding. Thirty‐eight patients were included, and 28 patients (74%) achieved hemostasis. The median dose of 4F‐PCC was 50 units/kg. In patients who achieved hemostasis, the median dose was 50 units/kg, and in those who failed to reach hemostasis, a median dose of 30 units/kg was seen. Within the subgroup analysis, there was no difference in overall rates of hemostasis between the 4F‐PCC and andexanet alfa groups. Remaining a reasonable option to utilize for reversal of oral factor Xa inhibitors is 4F‐PCC, especially when andexanet alfa is unavailable, with 50 units/kg appearing to be the most effective dose to achieve hemostasis. Further studies are needed to determine a preferential agent.